2007
DOI: 10.1021/bi700776e
|View full text |Cite
|
Sign up to set email alerts
|

Domain 2 of Nonstructural Protein 5A (NS5A) of Hepatitis C Virus Is Natively Unfolded

Abstract: Nonstructural protein 5A protein (NS5A) of hepatitis C virus (HCV) plays an important role in the regulation of viral replication, interferon resistance, and apoptosis. HCV NS5A comprises three domains. Recently the structure of domain 1 has been determined, revealing a structural scaffold with a novel zinc-binding motif and a disulfide bond. At present, the structures of domains 2 and 3 remain undefined. Domain 2 of HCV NS5A (NS5A-D2) is important for functions of NS5A and involved in molecular interactions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
64
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 63 publications
(122 reference statements)
3
64
0
2
Order By: Relevance
“…(D1), two additional domains (D2 and D3) that are mainly intrinsically disordered (23)(24)(25) and that we previously characterized by NMR spectroscopy (27,28). IDPs/IDRs exist as highly dynamic and interconverting conformers and thus escape to the rule "one three-dimensional structure, one function."…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(D1), two additional domains (D2 and D3) that are mainly intrinsically disordered (23)(24)(25) and that we previously characterized by NMR spectroscopy (27,28). IDPs/IDRs exist as highly dynamic and interconverting conformers and thus escape to the rule "one three-dimensional structure, one function."…”
Section: Discussionmentioning
confidence: 99%
“…Crystallographic studies revealed that this domain could adopt at least three different homodimeric conformations (19 -21), underscoring the multifunctionality of the protein. By using several biophysical techniques such as NMR spectroscopy, circular dichroism, and gel filtration chromatography, NS5A-D2, which is essential for viral RNA replication (12), and NS5A-D3, which is involved in production and assembly of new virions (13,22), were shown to be mainly disordered (23)(24)(25). In this respect, NS5A is the HCV protein with the highest percentage of its primary sequence predicted to be disordered (26).…”
Section: Hepatitis C Virus (Hcv)mentioning
confidence: 99%
“…2A). As these anomalous chemical shifts were present equally in the genotype 1a NS5A-D2 domain (37), and as this Trp 312 -Ala 313 segment, as well as Pro 310 and Pro 315 , is fully conserved in all genotypes (Fig. 1A), we have synthesized a peptide centered on this motif and are currently pursuing a detailed NMR analysis to interpret the anomalous chemical shift values in structural terms.…”
Section: Discussionmentioning
confidence: 99%
“…NS5A-D2 and -D3, for which sequence conservation among HCV genotypes is significantly lower than for D1, have been proposed to be natively unfolded domains (28,32). Molecular and structural characterization of NS5A-D2 from HCV genotype 1a has confirmed the disordered nature of this domain (36,37).…”
Section: Hepatitis C Virus (Hcv)mentioning
confidence: 99%
“…Domain I is essential for RNA repli-cation and has a zinc-binding motif, and the domain is a dimer as determined by crystallography (27). Domains II and III are less conserved and natively unfolded (28)(29)(30). Domain III is required for proper assembly of viral particles (31) but is not needed for RNA replication (32).…”
Section: Hronic Liver Disease Caused By the Hepatitis C Virus (Hcv)mentioning
confidence: 99%